2002
DOI: 10.1006/lich.2002.0377
|View full text |Cite
|
Sign up to set email alerts
|

Use of 14C/C Ratios to Provide Insights into the Magnitude of Carbon Turnover in the Crustose Saxicolous Lichen Caloplaca Trachyphylla

Abstract: Abstract14C/C ratios in samples from radial transects across individual thalli of Caloplaca trachyphylla collected at two sites were measured and the results used to investigate whether 14C/C data might provide some insight into the magnitude of carbon turnover in this lichen species. The 14C/C data suggest that significant internal recycling/translocation of carbon is unlikely in the sampled thalli. However, converting the 14C/C data for the larger intact thalli sampled at each site to calendar years, using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…The results suggest there is not a statistically significant difference in the Table 3 Average radiocarbon (∆ 14 C) data from lichens analyzed in this study and reported by Bench et al (2001Bench et al ( , 2002 Table 5. The data provides no evidence of a significant difference between the δ 13 C values for the Caloplaca and Lecania species when comparing their isolated calcium oxalate pruina separated from the lichen tissues, the lichen tissues themselves, nor the δ 13 C tis − δ 13 C ox differences for the 2 species.…”
Section: ∆ 14 C Values Of Lichens Growing On Limestone and Sandstonementioning
confidence: 52%
See 3 more Smart Citations
“…The results suggest there is not a statistically significant difference in the Table 3 Average radiocarbon (∆ 14 C) data from lichens analyzed in this study and reported by Bench et al (2001Bench et al ( , 2002 Table 5. The data provides no evidence of a significant difference between the δ 13 C values for the Caloplaca and Lecania species when comparing their isolated calcium oxalate pruina separated from the lichen tissues, the lichen tissues themselves, nor the δ 13 C tis − δ 13 C ox differences for the 2 species.…”
Section: ∆ 14 C Values Of Lichens Growing On Limestone and Sandstonementioning
confidence: 52%
“…Moreover, the 14 C values from the limestone samples are consistently greater than values obtained by Bench et al (2001;2002) from analyses of Caloplaca trachyphylla (mean 14 C = 175.8 ± 70.5‰) growing on sandstone and Rhizocarpon geographicum (mean ∆ 14 C = 152.6 ± 19.8‰) growing on siliceous rocks (Table 3). Thus, the limestone specimens have more atmospheric carbon that must have been incorporated during an earlier period when the atmospheric 14 CO 2 concentration was higher (due to bomb 14 C production).…”
Section: ∆ 14 C Values Of Lichens Growing On Limestone and Sandstonementioning
confidence: 77%
See 2 more Smart Citations
“…As a consequence, any translocation towards the lobe tip would be against a significant concentration gradient. More direct studies of translocation employing C-14/C ratios in radial transects across lichens (Bench et al 2002) also suggest that significant internal recycling and translocation of carbon is unlikely. Hence, factors other than the movement of carbohydrate may be necessary to explain the growth ratesize curves of foliose lichens.…”
Section: Models Based On Translocation Within the Thallusmentioning
confidence: 96%